German Foreign Direct Investment and Wages - Stefan Lochner; Udo Broll (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
Over the last decade, German multinationals created about two million jobs abroad with increasing foreign direct investment (FDI). While there are many reasons for firms to go multinational and probably just as many for Germany's high unemployment, this paper aims to investigate the relationship between domestic labour costs and foreign direct investment. We apply a theoretical model for an econometric analysis examining the determinants of FDI using panel data of German firms' foreign capital stocks in 22 countries between 1994 and 2003. Estimating elasticities, we find that while domestic wages do not significantly influence total FDI by German firms, they positively affect the FDI stock in countries where cheap labour is abundant. Thus, although Germany's high labour costs are not the sole driver of foreign direct investment, they may accelerate the outsourcing of German jobs.
Keywords: F23; F21; F16; 330; Foreign direct investment; wages; trade; German multinational firms; Direktinvestition; Auslandsproduktion; Lohn; Arbeitskosten; Schätzung; Deutschland